Interpersonal violence against women in the State of Ceará from 2009 to 2018: an ecological study (Research, Society and Development, 2021)
Objective: To analyze the trend of interpersonal violence against women in the State of Ceará from 2009 to 2018. Methods: This is an ecological time series study on reported cases and mortality from violence against women. Four groups of variables were selected for analysis: profile of the victim/case, types of violence, mechanisms of action and aggressor. For trend analysis, the simple linear regression model was adopted. Results: From 2009 to 2018, there were 19,135 cases of violence against women. Over the years, there was an increase of 95.1% in the number of notifications. There was a statistically significant association between mortality rates and years of study (p=0.0024), indicating an annual increase of 0.5885. The prevalence coefficient showed an annual increase - relevant - of 11.5188 (p